Mammographic and ultrasound features of invasive lobular carcinoma of the breast. Issue 1 (5th June 2013) - Porter, Alan J; Evans, Elizabeth B; Foxcroft, Loani M; Simpson, Peter T; Lakhani, Sunil R
Abstract Introduction Invasive lobular cancer (ILC) is an important contributor to false negative mammography. This study aims to assess the value of digital mammography and to identify imaging features that could assist the radiologist to suggest the diagnosis of ILC prior to biopsy. Methods Three hundred sixty‐one cases of pure ILC diagnosed at the Wesley Breast Clinic during the period 1995–2010 were reviewed by one of the authors (AP). Radiological features were categorized, and clinical features and needle sampling results were recorded. Results Mammography was negative in 29.9% of ILCs. The commonest positive finding was a localized spiculated mass (41.8%). Thirty‐four point nine per cent of lesions were visible in only one view, usually cranio‐caudal. Calcification was not a feature of ILC. The use of digital mammography in 30% of cases did not decrease the false negative rate for ILC. Breast ultrasound (BUS) showed an abnormality in 97.8%, most commonly a localized irregular hypoechoic mass with shadowing. Conclusions Digital mammography does not reduce false negative mammography in ILC. The poor visibility of ILCs may be partly related to their low density (mass/unit volume). ILCs may sometimes be poor attenuators of X‐rays but excellent attenuators of ultrasound, causing marked acoustic shadowing. Bilateral whole BUS has a very low false negative rate in experienced hands and is mandatory in symptomatic women. The combination of poor visibility on mammography with high visibility on ultrasound, as well as certain characteristic ultrasound appearances of ILC, may enable the radiologist to suggest ILC as a diagnostic possibility, prior to biopsy.